IMPLEMENTASI COGNITIVE-BHEHAVIOUR THERAPY (CBT) UNTUK MEMBANTU MEMULIHKAN KESEHATAN MENTAL SISWA KORBAN BULLYING DI MADRASAH ALIYAH ABDUL AZIZ - khuzaimah; Imaratul Uluwiyah; Ika Romika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Mental health are a state in which a person doesn’t experience symptoms of mental disorders. A person with good mental health can live a normal life, especially when facing various life problems by being able to cope with stress. The CBT (Cognitive Behavioral Therapy) counseling approach helps students change negative thoughts into positive ones. This counseling is carried out one-on-one, in which a group of people experiencing the same problem participates. This approach focuses on changing negative thoughts into more positive thoughts. This CBT technique is very effective in dealing with mental health problems in students. The purpose on this study was to determine an application of Cognitive Behavioral Therapy in helping the mental health recovery of students who were victims of bullying at MA Abdul Aziz Curah Lele Jember, to determine the forms of bullying that occurred, and to determine an impact of bullying on students' mental health at MA Abdul Aziz. This study adopted a quantitative method with a single-case experimental design called A-B-A, which consists on three stages: the baseline stage, the intervention stage, and the follow-up stage. The results of this study are in the form of a scientific article that can be published in a national journal and later can be recommended to Islamic boarding school managers to improve the mental health of students who are victims of bullying at MA Abdul Aziz Curah Lele.